Contagion Influence on Trade and Investment Policy: A Network Perspective - Koka, Balaji R.; Prescott, John E.; Madhavan, Ravindranath (Journal of International Business Studies, 1999)
Adopting a network perspective, we demonstrate that two different, yet complementary, forces influence the formation of trade and investment policy. One the one hand, nations that are trading partners develop similar policies through a process of close and enduring interaction. On the other hand, nations that compete for trading opportunities adopt comparable policies through a process of establishing similar types of relations with other nations, even though they may not have direct ties to each other. Implications for managers of multinational enterprises are developed.